ULTRASONOGRAPHIC CHANGES IN THE HYALINE CARTILAGE: EVALUATION OF SENSITIVITY AND SPECIFICITY IN EARLY GOUTY ARTHRITIS - A. V. Petrov; O. P. Prokopenko; A. A. Petrov; N. V. Matveeva (Научно-практическая ревматология)
A sonographic sign, such as linear hyperechoic inclusions or uric acid deposits in the hyaline cartilage, has been recently introduced into the system of gout classification criteria. At the same time, the differential diagnostic value of this sign in early gouty arthritis (GA) has not been adequately explored.Objective: to evaluate specificity and sensitivity for detecting linear hyperechoic inclusions in the differential diagnosis of early GA in comparison with the increased level of uric acid, the presence of subcutaneous tophi, and the identification of intraosseous cysts at radiography.Subjects and methods. The investigators analyzed the data of examining 119 patients with arthritis with its symptom duration within 6 months at the stage of differential diagnosis. The following diagnoses were further established: GA in 32 patients, osteoarthritis (OA) in 28, rheumatoid arthritis (RA) in 28, and psoriatic arthritis (PsA) in 16. Along with clinical, laboratory, and radiological examinations, all the patients underwent ultrasonography (USG) of inflamed joints with an 18-MHz linear transducer to identify linear hyperechoic inclusions (urate deposits) in the hyaline cartilage.Results and discussion. Joint USG revealed urate deposits in 28 (87.5%) patients with GA, in 3 (10.7%) with OA, and in 1 (6.3%) with PsA. The sensitivity of the other signs of gout in early GA was 21.7% for intraosseous cysts, 25.0% for subcutaneous tophi, and 81.3% for hyperuricemia. The specificity of USG for urate deposits in GA was 94.4% and was comparable with that for the other signs of gout (86.1–98.6%). Conclusion. USG detection of urate deposits in patients with gout is characterized by high sensitivity and specificity for diagnosing GA within the first 6 months after the initial symptoms appear.